Adults and larvae of Skrjabinocerca canutus n. sp. (Nematoda: Acuariidae) from Calidris canutus rufa (Aves: Scolopacidae) on the southern Southwest Atlantic coast of South America - Diaz, Julia Inés; Cremonte, Florencia; Navone, Graciela Teresa; Laurenti, Sonia (Systematic Parasitology)
Adults and larvae of a new species of Skrjabinocerca Shikhobalova, 1930 (Nematoda: Acuarioidea) are described on the basis of light and scanning electron microscope studies. Specimens were recovered from Calidris canutus rufa Wilson (Aves: Scolopacidae) from the Southwest Atlantic coast of Uruguay. Data on the hosts, localities and main features of the four previously described species of the genus are provided. S. canutus n. sp. can be distinguished from its congeners by a combination of the following characters: non-recurrent cordons, shorter right spicule and possession of a delicate finger-like projection on the distal end of the left spicule. S. prima Shikhobalova, 1930 has a left spicule which is stilletto-shaped and sharply pointed, S. europaea Wong & Anderson, 1993 has recurrent cordons, S. americana Wong & Anderson, 1993 possesses two delicate digitiform projections on the distal end of its left spicule and S. bennetti Bartlett & Anderson, 1996 has subequal spicules. Fil: Diaz, Julia Inés. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Cremonte, Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Navone, Graciela Teresa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Laurenti, Sonia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...